THE EFFECT OF WORKLOAD AND COMPENSATION THROUGH WORK ENTHUSIASM ON EMPLOYEE LOYALTY - Wahyudi, Elsa; Syaodih, Erliany; Mulyani, Kahar (Universitas Islam Lamongan, 2024)
AMC Hospital faces the challenge of maintaining service quality while efficiently managing human resources. Employee loyalty, which encompasses their commitment and dedication to the company, is crucial in achieving organizational goals. The reciprocal relationship between the company and its employees, where the company provides means to meet employee needs while employees contribute to achieving the company's goals, forms the foundation of employee loyalty. This study aims to determine the influence of workload and compensation on employee loyalty, mediated by work enthusiasm. This research uses a quantitative approach with a cross-sectional design. Workload has a negative and significant effect on loyalty, where higher workload leads to lower employee loyalty. Compensation also has a negative effect on loyalty, indicating that increasing compensation does not necessarily increase loyalty. Work enthusiasm has a significant positive impact on loyalty. Lastly, work enthusiasm partially mediates the effect of workload and compensation on loyalty, though it does not entirely eliminate the negative impact of these two factors.